Silencing of long noncoding RNA XIST attenuated Alzheimer's disease‐related BACE1 alteration through miR‐124. (26th November 2019) - Yue, Du; Guanqun, Gao; Jingxin, Li; Sen, Suo; Shuang, Liu; Yan, Sun; Minxue, Zhang; Ping, Yin; Chong, Lu; Zhuobo, Zhang; Yafen, Wei
Abstract: Alzheimer's disease (AD) is a chronic progressive neurodegenerative disorder. However, its pathogenetic mechanism is still poorly understood. An increasing number of studies have evidenced the important role of long noncoding RNAs (lncRNAs) in AD. The aim of the current study was to investigate the effect and molecular mechanism of the lncRNA X‐inactive specific transcript (XIST) in AD. Bilateral common carotid artery occlusion (2VO) was used to induce an AD model in mice. Hydrogen peroxide (H2 O2 ) was used to induce an AD model in N2a cells. The lncRNA XIST, miR‐124, and BACE1 messenger RNA expression levels were detected by a real‐time polymerase chain reaction. The BACE1 protein expression level was detected by western blot and immunofluorescence assay. The Aβ1–42 expression level was detected using an enzyme‐linked immunosorbent assay kit. The expression level of lncRNA XIST was significantly upregulated in AD models, both in vivo and in vitro. Silencing of lncRNA XIST negatively regulated miR‐124 and positively regulated BACE1 expression in N2a cells, which is attenuated by cotransfection of anti‐miR‐124 oligodeoxyribonucleotide (AMO‐124). Silencing of lncRNA XIST reversed the effect of H2 O2 on miR‐124, BACE1, and Aβ1–42 expression in N2a cells, which was reversed by cotransfection of AMO‐124. Silencing of lncRNA XIST attenuated AD‐related BACE1 alteration through miR‐124. LncRNA XIST may be a new potential target for the treatment of AD.